Construing Reputation from Gender Diversity on Boards: Indian Evidence. Issue 2 (December 2017) - Kaur, Amanpreet; Singh, Balwinder
Corporate managers across the globe are on their toes to build favourable corporate reputation. Researchers have extricated many factors affecting corporate reputation. However, the role of gender diversity in enhancing corporate reputation is relatively an exotic area of research in emerging economies like India where women face vulnerable discrimination while contesting for board seats. The present study aims to unravel the relevance of female directors in convalescing corporate reputation by analysing data of 437 Indian companies in 2012, just prior to enactment of Companies Act, 2013. It was found that 60 per cent of the sample companies lack gender diversity and in fact employ no women director on the board. Results of multivariate regression analysis reveal that the presence of female on the board is perceived as a positive quality signal so as to enhance corporate reputation. The findings confer a motivation among Indian corporate managers to promptly adhere to the provisions of New Companies Act, 2013, mandating one woman director in boardroom, so as to procure benefits in terms of favourable corporate reputation. Baffled stakeholders can interpret women directors on the board as a clue to better governance and thereby perceive such companies propitiously.